(untitled) - McGuire, Kelly Ann (Hoboken, New Jersey, 2016)
Hotel Pricing in a Social World: How to Drive Value in the New Hotel Economy is an insightful resource that provides guidance on improving organizational decision making to keep your hotel relevant, from a pricing standpoint, in the often chaotic hotel landscape. This groundbreaking book clearly showcases the current environment of the hotel industry, and describes new and emerging trends that can impact your revenue management tactics. This essential text prepares you to survive and thrive in today's highly competitive market, and outlines the best approach to building profitable pricing strategies that follow both tactical and strategic best practices.
Keywords: Khách sạn,Hotels; Đánh giá,Rates